In Vivo Effects of Neostigmine and Physostigmine on Neutrophil Functions and Evaluation of Acetylcholinesterase and Butyrylcholinesterase as Inflammatory Markers during Experimental Sepsis in Rats - Diane I. Bitzinger; Michael Gruber; Simon Tümmler; Manuela Malsy; Timo Seyfried; Florian Weber; Andreas Redel; Bernhard M. Graf; York A. Zausig (Mediators of Inflammation)
Introduction. Recent studies have shown that acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) may serve as important diagnostic and therapeutic targets in sepsis. Since polymorphonuclear neutrophils (PMNs) play a pivotal role in the early phase of sepsis, we evaluated the potential therapeutic effects of cholinesterase inhibitors on PMN functions during cecal ligation and puncture- (CLP-) induced sepsis and investigated the roles of AChE and BChE as inflammatory markers under standardized experimental conditions. Methods. Sham surgery or CLP was performed in male Wistar rats (n=60). Animals were randomized into four groups: physostigmine, 100 μg/kg; neostigmine, 75 μg/kg; 0.9% saline (control group); and sham group, each applied four times over 24 h. The levels of reactive oxygen species (ROS) production and CD11b/CD62l expression were quantified by flow cytometry at t=0, 6, 15, 20, and 24 h. Blood gas analysis as well as AChE and BChE activity levels was measured by validated point-of-care measurements. Clinical scores and survival times were determined. Results. CLP induced a significant increase in ROS production and CD11b upregulation by rat PMNs. Treatment with physostigmine or neostigmine significantly reduced ROS production and CD11b upregulation by PMNs 20 h after CLP induction. In physostigmine-treated animals, survival times were significantly improved compared to the control animals, but not in neostigmine-treated animals. While AChE activity significantly decreased in the control animals at t>6 h, AChE activity did not change in the sham group. BChE activity decreased at t>20 h in the control animals. Conclusion. While AChE activity may serve as an acute inflammatory marker, BChE activity shows a delayed decrease. Administration of centrally acting physostigmine in CLP-induced sepsis in rats has protective effects on PMN functions and improves survival times, which may be of interest in clinical practice.